Analisis Potensi Peranan KH. Mahfudz Abdurrahman dalam Gerakan Angkatan Oemat Islam di Kebumen (1945-1950) sebagai Muatan Pembelajaran Sejarah Berbasis Profil Pelajar Pancasila dalam Kurikulum Merdeka - Sufi, Yusni Diana; Yuliati, Yuliati (Universitas Nahdlatul Ulama Blitar, 2025)
The Islamic Oemat Force (AOI) movement cannot be separated from the events of the struggle of the people of Kebumen to defend independence. The Islamic Oemat Force movement grew and developed under the leadership of KH Mahfudz Abdurrahman, who at that time was considered a father by the people of Kebumen. If we examine further the role of KH Mahfudz Abdurrahman in the history of the Islamic Oemat Force Movement in Kebumen in 1945-1950, it has the potential to be used as content in history learning to support the Pancasila Student Profile program. This research uses Kuntowijoyo's historical research method to examine the elements of the Strengthening the Pancasila Profile program contained in the history of KH Mahfudz Abdurrahman's struggle in the Islamic Oemat Force Movement. Based on the analytical study that has been carried out, KH Mahfudz's role in the Islamic Oemat Force Movement can be integrated into the values in the Strengthening Pancasila Student Profile program. The six aspects of values in the Strengthening Pancasila Student Profile program are reflected in the role of KH Mahfudz, namely faith, devotion to God Almighty and noble character, independence, mutual cooperation, global diversity, critical and creative reasoning. We find that KH Mahfudz's role has the potential to support history learning based on Strengthening the Pancasila Student Profile.